Effects of Trehalose Administration in Patients with Mucopolysaccharidosis Type III - Mobini, Moein; Radbakhsh, Shabnam; Kubaski, Francyne; Eshraghi, Peyman; Vakili, Saba; Vakili, Rahim; Abbasifard, Mitra; Jamialahmadi, Tannaz; Rajabi, Omid; Emami, Seyed A.; Tayarani-Najaran, Zahra; Rizzo, Manfredi; et al. (Current Medicinal Chemistry, 2024)
Background and Aim: Mucopolysaccharidosis type III (MPS III) is a rare autosomal recessive lysosomal storage disease (LSD) caused by a deficiency of lysosomal enzymes required for the catabolism of glycosaminoglycans (GAGs), mainly in the central nervous system. Trehalose has been proposed as a potential therapeutic agent to attenuate neuropathology in MPS III. We conducted a single- arm, open-label study to evaluate the efficacy of trehalose treatment in patients with MPS IIIA and MPS IIIB. Methods: Five patients with MPS III were enrolled. Trehalose was administrated intravenously (15 g/week) for 12 weeks. Health-related quality of life and cognitive function, serum biomarkers, liver, spleen, and lung imaging were assessed to evaluate trehalose efficacy at baseline and trial end (week 12). Results: TNO-AZL Preschool children Quality of Life (TAPQOL) scores increased in all patients, and the mean scores for quality of life were increased after the intervention. Serum GAG levels were reduced in all treated patients (however, the differences were not statistically significant). Alanine aminotransferase (ALT) levels were reduced in all patients post-treatment (p=0.0039). The mean levels of aspartate transaminase (AST) were also decreased after 12 weeks of treatment with Trehalose. Decreased serum pro-oxidant-antioxidant balance and increased GPX activity were observed at the end of the study. Decreases in mean splenic length were observed, whereas the liver volume did not change. Conclusion: Improvements in health-related quality of life and serum biomarkers (GAGs, liver aminotransferase levels, antioxidant status), as well as liver and spleen size, were found following 3 months of trehalose administration in patients with MPS IIIA and MPS IIIB.
Keywords: mucopolysaccharidosis IIIA